Virulence genes in Aeromonas spp. (Aeromonadales: Aeromonadaceae) isolated from Oreochromis spp. (Perciformes: Cichlidae) destined for human consumption in Mexico. - Ortega-Balleza, Jessica L. (2018)
The genus Aeromonas are widely distributed in aquatic ecosystems are Gram-negative rods, oxidase-positive, and glucose-fermenting, considered emerging pathogens in humans. Aeromonas belongs to the fish microbiota, these microorganisms have a diversity of virulence factors responsible for a variety of infections in humans mainly gastrointestinal diseases. The presence of Aeromonas in products intended for consumption with high commercial demand such as tilapia generates sanitary concern due to the pathogenic potential of this bacteria. In this context, identification of virulence genes in strains of Aeromonas isolated in Oreochromis spp. intended for human consumption in Reynosa, Tamaulipas, Mexico is important due to the lack of molecular studies in this geographical area. In the present study the pathogenic potential of 15 strains of Aeromonas (A. veronii, A. hydrophila and A. schubertii) from Oreochromis spp. for human consumption were analyzed. Through PCR six virulence genes were analyzed (alt, ast, aerA, hlyA, gcat and stx1) and the strains used as control were: Aeromonas hydrophila subsp. hydrophila ATCC 7966, Aeromonas caviae 429865 INP, Escherichia coli O157: H7 and Escherichia coli K12. El 100 % (n = 15) of the strains harbored at least one virulence gene, aerA gene was detected in 86.66 % of the analyzed strains, while ast and stx1 genes were not identified. Moreover, Aeromonas strains had associated genes in the same strain: aerA / gcat, alt / aerA, alt / aerA / gcat / hlyA and alt / aerA / gcat, of which aerA / gcat were observed mostly in A. veronii, while A. hydrophila had the highest associations. These findings indicate that the strains of Aeromonas isolated in Oreochromis spp. have the potential to cause human diseases, and therefore, this species used as food, could be a vehicle for infections caused by Aeromonas. It also allows to provide information on this emerging microorganism to effectively treat and control any epidemiological event caused by Aeromonas spp. in the future.